Effects of photoperiod on morphology and function in testis and epididymis of Cricetulus barabensis - Mou, Junjie; Xu, Jinhui; Wang, Zhe; Wang, Chuanli; Yang, Xueqi; Wang, Xingchen; Xue, Huiliang; Wu, Ming; Xu, Laixiang (Journal of cellular physiology, 2021)
Photoperiod regulates the seasonal reproductive rhythms of mammals by influencing the development and function of sexual organs; however, the underlying mechanism remains unclear. We examined the morphology and functioning of the main sex organs of striped dwarf hamsters (Cricetulus barabensis) under different photoperiods (short daylight [SD], moderate daylight [MD], and long daylight [LD]) and further investigated the underlying molecular mechanisms. There was an inverse correlation between blood melatonin levels and photoperiod in the order SD > MD > LD. Decreases in body and tissue weights were observed under SD, whereas testis and epididymis weights between MD and LD were comparable. The diameters of the spermatogenic tubules, thickness of the spermatogenic epithelium, and the number of spermatogonia and Sertoli cells decreased under SD, whereas the serum‐luteinizing hormone, follicle‐stimulating hormone, and fecal testosterone concentrations decreased under LD. In SD, bax/bcl2 protein expression increased in the testes and decreased in the epididymides, whereas LC3II/LC3I remained unchanged in the testes and increased in the epididymides compared with the MD group. In LD, bax/bcl2 and LC3II/LC3I protein expression levels were unchanged in the testes but were decreased in the epididymides. In SD and LD, adenosine triphosphate synthase and citrate synthase protein expression levels were unchanged in the testes but were decreased in the epididymides. Drp1 and Mff protein expression increased in the testes and decreased in the epididymides. Overall, different regulatory mechanisms in the testis and epididymis led to degeneration under SD and maintenance under LD, preferentially protecting mitochondrial function in the testis by regulating mitochondrial fission. Our findings confirm that short daylight (SD) exposure can lead to the loss of weight and structural degradation of sexual organs, whereas long daylight (LD) exposure decreased testicular‐related hormones, possibly leading to a weakening of the reproductive ability of male hamsters. The loss of sex organ weight under SD may be mainly caused by increases in apoptosis levels in the testes and autophagy levels in the epididymis. In addition, the stability of mitochondrial function in the testis and the decrease of the corresponding level in epididymis may be a molecular strategy for hamsters to protect testicular function under various photoperiods.